Company Law - Michael Ottley (Routledge, 2013)
Routledge QandAs give you the tools to practice and refine your exam technique, showing you how to apply your knowledge to maximum effect in assessment. Each book contains essay and problem-based questions on the most commonly examined topics, complete with expert guidance and model answers that help you to: Plan your revision and know what examiners are looking for: Introducing how best to approach revision in each subject Identifying and explaining the main elements of each question, and providing marker annotation to show how examiners will read your answer Understand and remember the law: Using memorable diagram overviews for each answer to demonstrate how the law fits together and how best to structure your answer Gain marks and understand areas of debate Providing revision tips and advice to help you aim higher in essays and exams Highlighting areas that are contentious and on which you will need to form an opinion Avoid common errors: Identifying common pitfalls students encounter in class and in assessment The series is supported by an online resource that allows you to test your progress during the run-up to exams. Features include: multiple choice questions, bonus QandAs and podcasts.